Implementasi Pompa Air Otomatis Tenaga Surya Untuk Rumah Ibadah - Yuhendri, Muldi; Aswardi, Aswardi; Hambali, Hambali (University of Islam Malang, 2020)
Clean water is one of the most vital needs for a mosque. Clean water is generally taken from wells using electric water pumps. The use of water pumps is often a problem in areas where the electricity network is often off, as happened in the Raya Mosque of Nagari Salareh Aia, Palembayan District, Agam Regency. To overcome this problem, a solar automatic water pump is designed which is equipped with a battery as a backup power supply and one phase inverter to convert the solar panel voltage to alternating voltage according to the voltage of the water pump motor. The water pump automation is designed using a floating switch installed in a water tank. This solar water pump is implemented using a 300 wp solar panel, a 90 Ah battery and a 1200 Watt inverter. This solar water pump is also equipped with a solar charger for charging and discharging batteries. Field test results show that the automatic solar water pump proposed in this service program has been working properly according to the plan.